Aspects of stepped-frequency processing for low-frequency SAR systems - Lord, Richard Thomas (Department of Electrical Engineering, 2024)
Ultra-wideband synthetic aperture radar (SAR) systems operating in the VHF/UHF region are becoming increasingly popular because of their growing number of applications in the areas of foliage penetration radar (FOPEN) and ground-penetrating radar (GPR). The objective of this thesis is to investigate the following two aspects of low-frequency (VHF/UHF-band) SAR processing: 1. The use of stepped-frequency waveforms to increase the total radar bandwidth, thereby increasing the range resolution, and 2. Radio frequency interference (RFI) suppression. A stepped-frequency system owes its wide bandwidth to the transmission of a group of narrow-bandwidth pulses, which are then combined using a signal processing technique to achieve the wide bandwidth. Apart from providing an economically viable path for the upgrading of an existing single frequency system, stepped-frequency waveforms also offer opportunities for RFI suppression. This thesis describes three methods to process stepped-frequency waveforms, namely an IFFT method, a time-domain method and a frequency-domain method. Both the IFFT method and the time-domain method have been found to be unsuitable for SAR processing applications. The IFFT method produces multiple "ghost targets" in the high resolution range profile due to the spill-over effect of energy into consecutive coarse range bins, and the time-domain technique is computationally inefficient on account of the upsampling requirement of the narrow-bandwidth pulses prior to the frequency shift. The frequency-domain technique, however, efficiently uses all the information in the narrowband pulses to obtain high-resolution range profiles which do not contain any "ghost targets", and is therefore well suited for SAR processing applications. This technique involves the reconstruction of a wider portion of the target's reflectivity spectrum by combining the individual spectra of the transmitted narrow-bandwidth pulses in the frequency domain. It is shown here how this method may be used to avoid spectral regions that are heavily contaminated with RFI, thereby alleviating the problem of receiver saturation due to RFI. Stepped-frequency waveforms also enable the A/D converter to sample the received narrow-bandwidth waveform with a larger number of bits, which increases the receiver dynamic range, thereby further alleviating the problem of receiver saturation during the presence of RFI. In addition to using stepped-frequency waveforms for RFI suppression, a number of other techniques have been investigated to suppress RFI. Of these, the notch filter and the LMS adaptive filter have been implemented and applied on real P-band data obtained from the E-SAR system of the German Aerospace Center (DLR), Oberpfaffenhofen, and on real VHF-band data obtained from the South African SAR (SASAR) system. Both methods significantly suppressed the RFI in the real images investigated. It was found that the number of range lines upon which the LMS adaptive filter could operate without adaptively changing the filter tap weights was often well above 100. This facilitated the re-writing of the LMS adaptive filter in terms of an equivalent transfer function, which was then integrated with the range-compression stage of the range-Doppler SAR processing algorithm. Since the range-compression and the interference suppression could then be performed simultaneously, large computational savings were achieved. A technique was derived for suppressing the sidelobes which arise as a result of the interference suppression of the LMS adaptive filter. This method was also integrated with the range-compression stage of the range-Doppler processor, leading to a very efficient implementation of the entire RFI suppression routine.